TNF-Alpha in Peripheral Neuropathy Patients with Impaired Glucose Regulation - Xia Li; Ju Zhu; Na Liu; Jie Liu; Zhecheng Zhang (Journal of Diabetes Research)
Impaired glucose regulation (IGR) is the prestate of diabetes; about 1/3 of IGR patients will develop to diabetes finally. In this study, we investigated the serum tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) levels in peripheral neuropathy impaired patients with impaired glucose regulation (IGR). A total of 70 IGR patients received the conventional nerve conduction test, including 30 patients with peripheral neuropathy (PN) and 40 patients without peripheral neuropathy (NPN). The other 40 healthy individuals were recruited as controls. The serum TNF-α and IL-6 in IGR patients were higher than in control group, and serum TNF-α and IL-6 levels in IGR-PN group were higher than in IGR-NPN group (27.7±17.8 versus 13.1±6.7 pg/mL and 18.1±17.7 versus 6.4±3.7 pg/mL, resp., both p<0.05). Multifactors logistic regression analysis showed that TNF-α (OR = 0.893; p=0.009) was an independent factor affecting whether IGR could combine with peripheral neuropathy. TNF-α and IL-6 could aggregate peripheral neuropathy in impaired glucose regulation patients; TNF-α might be independent risk factor for peripheral neuropathy in glucose regulation impaired patients.